PENGARUH SISTEM HUKUM ISLAM TERHADAP POLITIK HUKUM NASIONAL - Islamiyati, Islamiyati (Diponegoro Private Law Review, 2018)
Islamic law is one of the legal systems in Indonesia. The emergence of the theory of the application of Islamic law and the majority of the people of Indonesia using Islamic law, can be used as a basis for political power in determining and choosing Islamic law in order to achieve national development goals. The study will analyze the influence of the Islamic legal system on national legal politics. The benefits can be understood the influence and existence in the implementation of national law. This type of research is library research, the method of approach is juridical normative, with secondary data sources which include primary, secondary and tertiary legal materials. Data is analyzed qualitatively. The results of the study describe the influence of Islamic legal systems can realize the values of most Indonesian people, become a material source of legal formation to fill legal vacancies, become a tool to solve legal problems, protect human rights, provide legal contributions from the formation of national legal spirit, participate in realizing tolerance on the basis of humanity in legal pluralism in Indonesia. Keywords: Legal System, Islamic Law, Legal politic